Rural Enterprise Hub Supporting Rural Entrepreneurship and Innovation – Case Studies from Hungary - Katonáné Kovács Judit; Zoltán Erzsébet Szeréna (European Countryside, 2017)
Although the tendency that the population migrate from rural to urban areas is typical world wide, the globalised economy creates new circumstances and opportunities for rural areas as well. The ‘new rural economy’ therefore needs new infrastructure to support it. The authors of the paper have a common interest in how enterprise hubs could help the development of entrepreneurship in the 21st century from two different directions, from physical and from social aspects. Building on the experience gained along enterprise hubs in cities, the hypothesis behind the study is, that creating enterprise hubs from existing buildings in rural settlements could help the development of rural entrepreneurship. To examine the hypothesis two case studies following a period of two years (enterprise hub development in Debrecen and Noszvaj) were carried out. In line with other studies in this field, result shows that even well-designed physical spaces are not enough for change, and initiators, hosts or facilitators are needed, as they play an important role in focusing on the real interaction network and enabling more synergies to happen.